Business Ethics and Ethics Education in American Business Programs - D. Keiser, John (Competitio, 2008)
This essay presents an overview of what American business programs cover in their curricula regarding ethics and the reasons behind teaching ethics-related material to business students. Topics for the paperinclude; requirements for having ethics in the curricula, broad perspectives of what constitutes ethical business practices, and the difference between professional ethics and business ethics.Journal of Economic Literature (JEL) classification: M14, A20